2000
DOI: 10.3354/meps199243
|View full text |Cite
|
Sign up to set email alerts
|

Determination of spawning areas and larval advection pathways for King George whiting in southeastern Australia using otolith microstructure and hydrodynamic modelling. II. South Australia

Abstract: Two hypotheses regarding the origin of post-larval Sillaginodes punctata that recruit to nursery areas in South Australia were assessed. These were that post-larvae originate either hundreds of kilometres to the west and are delivered by weather-determined ocean currents or they originate from numerous spawning grounds located only Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 15 publications
(35 reference statements)
2
31
0
Order By: Relevance
“…Recent studies have shown that autorecruitment was frequent in isolated coral zones (Galzin et al, 1998;Jones et al, 1999;Cowen et al, 2000;Fowler et al, 2000). It could account for a significant part in the fish recruitment of the Glorieuses Islands.…”
Section: Species Richnessmentioning
confidence: 99%
“…Recent studies have shown that autorecruitment was frequent in isolated coral zones (Galzin et al, 1998;Jones et al, 1999;Cowen et al, 2000;Fowler et al, 2000). It could account for a significant part in the fish recruitment of the Glorieuses Islands.…”
Section: Species Richnessmentioning
confidence: 99%
“…Seagrass beds typically provide juvenile whiting with protection from predation as well as being the habitat for numerous prey items. Research on this species has focused on migratory patterns (Fowler et al 2000;Fowler et al 2002), larval recruitment and settlement (Jenkins & May 1994;Hamer & Jenkins 1997;Moran et al 2004), and habitat usage (Connolly 1994;Jenkins & Wheatley 1998). However, very little is known about the response of this species to light level manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…Passive transport predictions, based on modelled estuarine hydrodynamics, are driven principally by tidal flux and wind-driven flows , Cox 2001). Circulation models have been successful in predicting larval transport entering from the ocean to an estuary in order to link larval pathways to the temporal (Jenkins & Black 1994, Brown et al 2004 and spatial variation , Fowler et al 2000 in recruitment. The 'passive-transport' approach has been effective on a spatial scale of tens of kilometres within the large open estuary of Port Phillip Bay, Victoria , and the more complex estuaries of Beaufort Inlet in North Carolina and Aransas Bay in Texas (Brown et al 2005).…”
Section: Introductionmentioning
confidence: 99%